2001
DOI: 10.1177/002215540104900816
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Mast Cell Tryptase in Neoangiogenesis of Premalignant and Malignant Lesions of the Uterine Cervix

Abstract: Recently, mast cell tryptase has been identified as another potent proangiogenic factor in tumors, along with fibroblast and vascular endothelial growth factors. Its role has been studied in a number of cancers, including carcinoma of the uterine cervix, with discordant results. Our aim was to study the expression of tryptase and bFGF in mast cells (MCs) during development of neoangiogenesis in premalignant and malignant lesions of the cervix. Biopsy specimens from 21 patients without cancer and from 63 patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
63
0
2

Year Published

2002
2002
2013
2013

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(75 citation statements)
references
References 8 publications
8
63
0
2
Order By: Relevance
“…In their study, Ranieri et al (36) reported that tryptase-positive mast cells positively correlated with angiogenesis in breast cancer. Further experimental evidence confirmed a correlation between angiogenesis and tryptasepositive mast cell counts in human endometrial (37) and invasive cervical cancers (38). Both parameters increased in accordance with tumor progression.…”
Section: Introductionsupporting
confidence: 54%
“…In their study, Ranieri et al (36) reported that tryptase-positive mast cells positively correlated with angiogenesis in breast cancer. Further experimental evidence confirmed a correlation between angiogenesis and tryptasepositive mast cell counts in human endometrial (37) and invasive cervical cancers (38). Both parameters increased in accordance with tumor progression.…”
Section: Introductionsupporting
confidence: 54%
“…Tryptase-positive mast cells increase in number and vascularization increases in a linear fashion in solid tumors, such as human malignant melanoma , endometrial carcinoma (Benítez-Bribiesca et al 2001, Ribatti et al 2005, breast cancer (Ribatti et al, 2007a;Ranieri et al, 2009), uterine leiomyomas (Ribatti et al, 2007b), colorectal cancer (Gulubova and Vlaykova, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…For almost 20 years, in vitro and in vivo studies have linked mast cell (MC) degranulation and activation with angiogenesis and neovascularization (Folkman 1982, Levi Schaffer & Pe'er 2001, Norrby 2002). This assumption is partially supported by the close anatomical association between MCs and the vasculature, and the recruitment of these cells during tumour growth, wound healing and inflammation (Benítez-Bribiesca et al 2001, Fukushima et al 2001, Norrby 2002. Moreover, degranulation of MCs by a variety of secretagogues causes the release of potent angiogenic factors, e.g.…”
Section: Introductionmentioning
confidence: 99%